Minor variant of AHSG gene 767C>G polymorphism may decrease the risk of gestational diabetes mellitus. (2nd April 2020) - Akbas, Halit; Kahraman, Suna; Sak, Sibel; Akkafa, Feridun
Abstract: Insulin resistance plays a central role in the development of gestational diabetes mellitus (GDM). The fetuin A molecule, of which serum level increases during pregnancy, is an inhibitor of insulin receptor tyrosine kinase and it is associated with insulin resistance. The aim of this study is to research the relationship of –843A>T (rs2248690) and 767C>G (rs4918) polymorphisms in the alpha-2-Heremans Schmid glycoprotein (AHSG) gene which is responsible for the synthesis of fetuin A and its association with (GDM). In this study, 83 pregnant women with GDM who applied to the Obstetrics and Gynaecology Clinics and 100 normal pregnants enrolled as the control group. Genotyping of AHSG gene polymorphisms was performed by using the TaqMan allelic discrimination kit with real time PCR device. In our study, homozygous GG genotype which was polymorphic in the 767C>G polymorphism of AHSG gene was found significantly low in the patient group ( p  < .05). Genotype distribution of AHSG gene –843A>T polymorphism was not statistically significant between the patient and control groups ( p  > .05). Our results showed that homozygous GG variant of AHSG gene 767C>G polymorphism may have protective effect against the development of GDM. Impact statement: What is already known on this subject ? Insulin resistance has a central role in the development of gestational diabetes mellitus (GDM). The fetuin A molecule is an inhibitor of insulin receptor tyrosine kinase and it is associated with insulin resistance. The –843T>A and 767G>C polymorphisms of AHSG gene encoding fetuin A are affects serum fetuin A level. In a single study investigating the relationship between GDM and AHSG gene 767G>C polymorphism, there was no significant difference in genotype distribution but it was reported that the frequency of G allele increased in GDM group and this increase provided a weak risk or predisposition. What the results of this study add ? The present study revealed that homozygous GG variant of AHSG gene 767C>G polymorphism may decrease the risk of GDM. What the implications are of these findings for clinical practice and/or further research ? Protective effect of homozygous GG variant of AHSG gene 767C>G polymorphism, can be used as a molecular biomarker to predict the development of GDM. These results should be supported by further research in larger sample sizes.